Extraordinary jumping ability of the Red Forest Duiker Cephalophus Natalensis - V de Vos (Koedoe: African Protected Area Conservation and Science, 1979)
While catching game in the northeastern coastal area of Natal near False Bay, Lake St. Lucia, Republic of South Africa, we were forced to keep red forest duiker Cephalophus natalensis in a holding corral for short periods before translocation commenced.